Coinfection of Ixodes scapularis (Acari: Ixodidae) Nymphs With Babesia spp. (Piroplasmida: Babesiidae) and Borrelia burgdorferi (Spirochaetales: Spirochaetaceae) in Wisconsin. Issue 4 (15th April 2021) - Zembsch, T E; Lee, X; Bron, G M; Bartholomay, L C; Paskewitz, S M
Abstract: Borrelia burgdorferi, the spirochete that causes Lyme disease, is endemic and widespread in Wisconsin. Research in the northeastern United States has revealed a positive association between Babesia microti, the main pathogen that causes babesiosis in humans, and Bo. burgdorferi in humans and in ticks. This study was conducted to examine associations between the disease agents in the Upper midwestern United States. Ixodes scapularis Say nymphs ( N = 2, 858) collected between 2015 and 2017 from nine locations in Wisconsin were tested for Babesia spp. and Borrelia spp. using real-time PCR. Two species of Babesia were detected; Ba. microti and Babesia odocoilei (a parasite of members of the family Cervidae). Prevalence of infection at the nine locations ranged from 0 to 13% for Ba. microti, 11 to 31% for Bo. burgdorferi sensu stricto, and 5.7 to 26% for Ba. odocoilei . Coinfection of nymphs with Bo. burgdorferi and Ba. odocoilei was detected in eight of the nine locations and significant positive associations were observed in two of the eight locations. The prevalence of nymphal coinfection with both and Bo. burgdorferi and Ba. microti ranged from 0.81 to 6.5%. These two pathogens were significantly positively associated in one of the five locations where both pathogens were detected. In the other four locations, the observed prevalence of coinfection was higher than expected in all but one site-year. Clinics and healthcare providers should be aware of the association between Ba. microti and Bo. burgdorferi pathogens when treating patients who report tick bites.